Multiphysical modeling and development of an electromagnetic exciter of low-frequency oscillations as a converter of renewable energy sources - Tumanov I.Ye. (Горное оборудование и электромеханика)
An electromagnetic exciter of low-frequency mechanical oscillations (EME LFO) with a series-connected capacitor in its operating modes is presented. The aim of the study is the practical implementation of the generator mode of operation and its use as a converter of renewable energy sources of natural origin. To achieve the goal, multiphysical modeling of structural elements and components of the object of study, which were determined on the basis of a patent and license search for a prototype, was performed. An inductor in the form of a polarized relay was introduced into the design scheme, between the poles of which an anchor, fixed on a hinge, performs low-frequency oscillatory movements. Also considered is a converter circuit in which the anchor performs reciprocating movements in the internal cavity of a cylindrical inductance coil, in the circuit of which a capacitor is also series-connected. To convert the frequency of the supply voltage (50 Hz) at the input to the low-frequency range of mechanical oscillations, the parameters of the resonant circuit are adjusted. For practical implementation of the generator mode of the oscillation exciter, technical solutions for converting mechanical rotational motions of natural origin into reciprocating (oscillatory) motion are considered. The results of model studies of each structural element in the COMSOL MULTIPHYSICS software environment are presented: animations of simulating mechanical motions of natural origin as an input signal of the mechanical subsystem and an oscillogram of the resonance of the induced electric current in a series resonant circuit of an alternating current electric circuit at the output of the system. The object is presented as a functional model of an electromagnetic exciter of low-frequency mechanical oscillations as a circuit for successively converting mechanical energy of oscillatory motion into electrical energy.